2021
DOI: 10.1021/jacs.1c02145
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Covalent Organic Frameworks with Cobalt(II)-Phthalocyanine Sites for Efficient Electrocatalytic Carbon Dioxide Reduction

Abstract: The rapid development in synthesis methodology and applications for covalent organic frameworks (COFs) has been witnessed in recent years. However, the synthesis of highly stable functional COFs still remains a great challenge. Herein twodimensional polyimide-linked phthalocyanine COFs (denoted as CoPc-PI-COF-1 and CoPc-PI-COF-2) have been devised and prepared through the solvothermal reaction of the tetraanhydrides of 2, 3,9,10,16,17,23, with 1,4phenylenediamine and 4,4′-biphenyldiamine, respectively. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(186 citation statements)
references
References 70 publications
4
162
1
Order By: Relevance
“…The SEM images showed that ZnBCBTP@MWCNTs sample had tubular morphology, identical to that of the parent MWCNTs. Meanwhile, comparing to the pristine MWCNTs, ZnBCBTP@MWCNTs clearly presented that almost all MWCNTs are fully coated with ZnBCBTP due to their strong π-π interaction [24]. The results also were confirmed by the TEM images, Figure S1B.…”
Section: Structure and Morphology Characterizationsupporting
confidence: 59%
“…The SEM images showed that ZnBCBTP@MWCNTs sample had tubular morphology, identical to that of the parent MWCNTs. Meanwhile, comparing to the pristine MWCNTs, ZnBCBTP@MWCNTs clearly presented that almost all MWCNTs are fully coated with ZnBCBTP due to their strong π-π interaction [24]. The results also were confirmed by the TEM images, Figure S1B.…”
Section: Structure and Morphology Characterizationsupporting
confidence: 59%
“…[252,253] Many synthetic methods have been developed for the formation of 2D and 3D COFs, such as solvothermal, microwave, ionothermal, interfacial, and room-temperature methods. Solvothermal methods involve the reversible reaction of soluble monomers in a Pyrex tube of suitable volume at high temperatures (>100 °C), after degassing by multiple freeze-pump-thaw cycles, [254,255] whereas microwave methods are used to rapidly synthesize crystalline COFs within a short reaction time (<1 h). [256] An example of an ionothermal method is the synthesis of covalent triazine frameworks in molten ZnCl 2 (as the solvent), where the latter also mediates the required trimerization reaction, [257] whereas the interfacial method involves the synthesis of COFs as thin films at the interface of two immiscible solvents.…”
Section: Opportunities For the Use Of Icofs In Energy Devicesmentioning
confidence: 99%
“…b,c) Electrocatalytic performances of the samples. Reprinted with permission [35] . Copyright 2021 American Chemical Society.…”
Section: Electrocatalytic Co2rrmentioning
confidence: 99%